Fatigue severity in World Trade Center (9/11) responders: a preliminary study. Issue 2 (2nd April 2016) - Friedberg, Fred; Adamowicz, Jenna L; Caikauskaite, Indre; Napoli, Anthony; Shapira, Oren; Hobbs, Megan; Bromet, Evelyn; Kotov, Roman; Gonzalez, Adam; Clouston, Sean; Luft, Benjamin
ABSTRACT: Purpose : To assess fatigue severity in World Trade Center (9/11) responders 13 years later. Methods : The participant pool consisted of male 9/11 responders enrolled in the Stony Brook World Trade Center Health Program (WTC-HP), one of five centers of excellence established by the Centers for Disease Control and Prevention. Fatigue severity was assessed with the Fatigue Severity Scale. WTC-related medical conditions were certified by a physician and diagnoses of 9/11-related post-traumatic stress disorder (PTSD) and major depressive disorder (MDD) were determined with the Structured Clinical Interview for DSM-IV (SCID). Results : High fatigue severity was reported by 20.8% of the sample ( N = 1079) and was significantly associated with PTSD, major depressive disorder, sleep apnea, gastro-esophageal reﬂux disease, upper respiratory disease, and lower respiratory disease. These associations remained significant for PTSD, major depressive disorder and lower respiratory disease when adjusted for medications, age and BMI. Only 17.3% of the high fatigue subgroup did not have an identified medical or psychiatric diagnosis. Fewer fatigued (21.1%) than non-fatigued (72.0%) responders rated their physical health as 'good' or 'very good.' Also fewer fatigued (33.9%) than non-fatigued (54.1%) responders were employed full-time ( p < .0001). Conclusions : This study found clinically elevated fatigue in a high percentage of a male WTC responder cohort that prior to 9/11/2001 would be considered a 'healthy worker cohort.' To better understand the pathophysiology of fatigue, newer methodologies such as symptom provocation (e.g. exercise) designs may be useful.